Measurement of mixing enthalpies for Bi-Zn lead-free solder system - Singh V.; Jaiswal D.; Pathote D.; Singh K.K.; Behera C.K. (My University, 2025)
Integral mixing enthalpy, partial mixing enthalpy & interaction parameters of the Bi-Zn alloys system has been calculated at 823 K and 923 K by using the drop calorimetric technique. This will help to predict the thermodynamic properties of multi-component systems by using values of interaction parameters of the Bi-Zn binary system. It is widely recognized that high concentrations of any elements can lead to toxicity; however, Sn and Zn are relatively less hazardous due to their essential roles in the human diet. Bi is low-risk metal with a history of medical use. So it may be a good replacement for lead-based solder alloys as lead is a very toxic element. Argon gas is used as a carrier and auxiliary gas to provide an inert atmosphere in the furnace. It is also visible that the enthalpy of mixing is asymmetrical with a composition of Zn. The integral enthalpy of mixing of the Bi-Zn system at 823 K and 923 K is endothermic in nature all through the composition, and its most value at xZn = 0.79 is 3717.035349 Jmol− 1 and 3780.695484 Jmol− 1 respectively. The theoretical Redlich-Kister polynomial substitutional solution model was applied to the data from these measurements in order to find the binary interaction parameter by least-square fitting. When the estimated and measured values are compared, it is found that there is a good agreement between them. Copyright © 2023 Elsevier Ltd. All rights reserved.